UTAUT: Analysis of Usage Level of Android Applications as Learning Media in Indonesian Educational Institutions - Vera Mandailina; Saddam Saddam; Malik Ibrahim; Syaharuddin Syaharuddin (IJECA (International Journal of Education and Curriculum Application), 2019)
This study aims to analyze the application of android applications as a medium of mathematics learning in Indonesian educational institutions using the Unified Theory of Acceptance and Use of Technology (UTAUT) method both among teachers in delivering mathematical material and students in experimenting or completing school assignments. The research method used was descriptive quantitative with a four option Likert Scale questionnaire as a research instrument. Surveys were deployed using the Google Form-based Black Box system throughout Indonesia through Social Media. Based on the results of data analysis obtained information that the application of android applications as a learning media for mathematics in Indonesia is still below 50%. The effect of performance expectancy, effort expectancy, and social influence on behavioral intention is illustrated by the regression equation Y1 while facilitating the regression equation Y2 represents conditions and behavioral intention towards use behavior.